Analisis Studi Kelayakan Bisnis pada Usaha Chicken Holic - Vientiany, Dini; Adhelia, Dhea Putri; Shaqina, Maheza; Ginting, Nabilah Azzahra Amin Br (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to evaluate the business feasibility of Chicken Holic, a modern crispy chicken outlet targeting students and young workers. The research methodology involves a comprehensive business feasibility study approach, covering various aspects such as market and marketing, legal, technical and operational, managerial, financial, sharia and halal, socio-economic, and environmental aspects. Information was collected through a survey of 57 respondents and analysis of relevant documents. The findings indicate that Chicken Holic is highly feasible from a financial perspective, with a BEP of 49 servings per day, a net profit of IDR 15,350,000 per month, an ROI of 614% per year, and an investment return period of 1.95 months. In terms of the market, 64.9% of respondents considered the product price to be standard and affordable. This business is also in line with sharia principles, as it uses halal-certified raw materials, has a positive social impact through the employment of local workers, and adopts environmentally friendly waste management practices. Based on the analysis conducted, Chicken Holic is deemed feasible to operate with significant growth potential.